Stress resistance in naturalised waste water E. coli strains. Issue 2 (11th April 2017) - Zhi, Shuai; Banting, Graham S.; Ruecker, Norma J.; Neumann, Norman F.
Abstract : The authors recently demonstrated that naturalised strains of Escherichia coli exist in municipal waste water, characterised by ( a ) biomarker patterns in intergenic regions distinct from human and animal E. coli strains and ( b ) an insertion element ( IS30 ) located in the uspC – flhDC intergenic region of the genome. Remarkably, these strains are naturally adapted to survival and growth in waste water and differentially survive the treatment process. The authors sought to explore the adaptive mechanisms used by these strains for survival. A serial stress experiment (nutrient deprivation and osmotic stress followed by chlorine treatment) was performed and survival was measured using culture. Waste water strains were shown to be approximately 100 times more resistant to chlorine treatment than a wild-type human faecal strain. Naturalised waste water strains were also more robust at producing biofilms – an adaptive strategy for surviving environmental stressors. Since biofilm formation has been linked to increased motility, the authors examined the expression of the flagellar regulator gene, flhDC, under serial stress conditions. Chlorine was a potent inducer of flhDC expression in waste water strains. The results demonstrate that waste water strains possess adaptive genotypic/phenotypic properties related to their survival in waste water and challenge the understanding of treatment reduction based on E. coli as an indicator of treatment performance.